ChemInform Abstract: Solvothermal Synthesis of One‐Dimensional Chalcogenides Containing Group 13 Elements. Issue 12 (14th March 2013) - Ewing, Sarah J.; Romero, M. Lucia; Hutchinson, Jack; Powell, Anthony V.; Vaqueiro, Paz
Abstract [H2dach][GaS2]2, [H2dach][Ga2Se3(Se2)], and [H2dach] [Ga2‐xInxSe3(Se2)] (0 < x < 2) are solvothermally synthesized using gallium, indium, sulfur, selenium, and trans‐1, 4‐diaminocyclohexane (dach) as starting materials, and 1, 2‐diaminocyclohexane, MeOH, and water as solvents (autoclave, 170 °C, 10 d).